Muhammad Ali Shams Addin the Poet of Vision and Nihilism ‎Secret Poem to my Belooved Asya‎ - Nadi Al-Deek (My University, 2005)
Mohamed Ali Shamsiddin is one of those distinct poetic sounds in his local and Arab environments, since he awakens the spirit, and makes the ideas correlated with the geometrical structure of the poem. All of that shows coherent structure in both the pattern and the content Shamsiddin maintained the contemporary Arab pattern of the poem, and also preserved the importance of the rhythm and music in the poetic structure, in addition to the contents derived from the caves of the environment and the agonies of the others. Thus, Shamsiddin's poem continues to preserve its substance, and humanitarian and sensual pulses which consequently add to its beauty and splendor. In this sense, we can touch the traditional symbols and values; at the same time we can feel the contemporary zeals, both correlated with one another to materialize one artistic vision, rich in its symbols, vocabulary’s, expressions, and the griefs of the others. Thus, we can see that he makes himself by this art which is renewed in its performance and firmness, in its positive and constructive data towards his subject and readers. For all of the above mentioned, this study is made for his volume first of poetry (Qasaed Muharraba I/a Habikati Asia).because this work is one of the distinguished bridges in its high quality, and its performance in creating the case of correlation between self and art, self and the others.

محمد علي شمس الدين من الأصوات الشعرية المعاصرة المتميزة في محيطه المحلي والعربي، لأنه ينهض الذات ويجعل الأفكار تتلازم مع البناء الهندسي للبناء الشعري، مما يرينا بناءً محكما في الشكل والمضمون، حيث حافظ على شكل القصيدة العربية المعاصرة، وأيقن أهمية الإيقاع والموسيقا في الجسد الشعري، والمضامين المنتزعة من هموم المحيط وعذابات الآخرين، لذا غدت قصيدته تحافظ على كينونتها ودفقاتها الشعورية الإنسانية حتى تتعد د الجماليات فيها، فنرى التراث ببعض قيمه ورموزه، والمعاصرة واندفاعاتها تتلازمان في نسق واحد كي تتجسد رؤية فنية عبقة، برموزها وصورها ومفرداتها اللغوية وهموم الآخرين، لذا نجده يمايز ذاته بفنه المتجدد في الأداء والثبات في المعطيات الايجابية البناءة تجاه موضوعه، من هنا جاءت فكرة القراءة في ديوانه الأول ""قصائد مهربة إلى حبيبتي آسيا"" لأنه يشكل أحد الجسور المتينة والمتميزة في الجودة والأداء في خلق حالة المواءمة بين الذات والفن، والفن والمجموع.
محمد علي شمس الدين – شاعر الرؤيا والعدم – قراءة نقدية في ديوانه الأول – قصائد ‏مهربة الى حبيبتي آسيا